Positive perceptions of brown bears linked to long-term cohabitation in the Iberian Peninsula - Pedro Severino; Mariana Graça; Nuno Negrões; Tânia Barros; João Carvalho; Eduardo Ferreira; Roberto Hartasánchez; Bruno Malheiro; Luís Miguel Rosalino; Rita Tinoco Torres; Jenny Anne Glikman (Scientific Reports, 2025)
Abstract The brown bear (Ursus arctos) populations are expanding in the Iberian Peninsula, particularly in the Cantabrian Mountains. This ongoing expansion and the species’ return to Portugal could be jeopardized by a lack of sustainable coexistence strategies. To shed light on how experiences with bears have shaped human perceptions and attitudes toward this species, we distributed online questionnaires (n = 441) across Portugal and Spain. In addition, we evaluated differences in attitudes and perceptions among regions with varying levels of exposure to bears: those with (BAS) or without (NBAS) bear presence in Spain and those with (BAP) or without (NBAP) the potential to sustain bears in Portugal. Despite observing overall positive attitudes toward bears, Spanish respondents showed stronger attachment and receptiveness toward the species. Respondents from BAS, having more interactions with wild bears, were also more favourable toward sharing territory with them. Conversely, Portuguese respondents showed more neutral attitudes toward bear presence, as well as higher perception of risk and lower perception of benefit than previously reported. Our findings highlight the importance of understanding the social landscape in bears’ expansion range. As human-bear interactions increase, this knowledge is key to adopt proactive and targeted socio-ecological measures to address local community’s concerns.